Time-resolved and XUV spectroscopy of helium nanodroplets. (August 2015) - Mudrich, M; von Vangerow, J; LaForge, A; Stienkemeier, F; Ciavardini, A; O'Keeffe, P; Ovcharenko, Y; Möller, T; Drabbels, M; Piseri, P; Plekan, O; Finetti, P; et al.
Synopsis: The ultrafast dynamics of pure and doped helium nanodroplets is studied using VIS and XUV femto-second pump-probe spectroscopy in combination with ion and electron imaging detection.